Functional immune boosters; the herb or its dead microbiome? Antigenic TLR4 agonist MAMPs found in 65 medicinal roots and algae’s - Mazzio, E.; Barnes, A.; Badisa, R.; Fierros-Romero, G.; Williams, H.; Council, S.; Soliman, K.F.A. (Journal of Functional Foods, 2023)
[Display omitted] •Humans have been consuming medicinal plants to combat human illness for centuries while ascribing beneficial effects to the plant.•Yet, medicinal plants contain a distinct and separate microbiome - which when inactivated is not removed from botanical products.•Antigenic microbial debris as MAMPs in certain botanical supplements are immune stimulants, liken to vaccines adjuvants.•Few studies have examined a large number of plants to discern those with high concentration of bio-active MAMPS.•In this work, we identify 65 out of 2000+ tested with high TLR4 agonist MAMP presence and investigate the plant vs. the microbiome. Humans have been consuming medicinal plants (as herbs/ spices) to combat illness for centuries while ascribing beneficial effects predominantly to the plant/phytochemical constituents, without recognizing the power of obligatory resident microorganism’ communities (MOCs) (live/dead bacteria, fungus, yeast, molds etc.) which remain after industrial microbial reduction methods. Very little is known about the taxonomic identity of residual antigenic microbial associated molecular patterns (MAMPs) debris in our botanical over the counter (OTC) products, which if present would be recognized as foreign (non-self) antigenic matter by host pattern recognition receptors (PRRs) provoking a host immune response; this the basis of vaccine adjuvants. As of today, only few research groups have removed the herbal MAMP biomass from herbs, all suggesting that immune activation may not be from the plant but rather its microbial biomass; a hypothesis we corroborate. Purpose: The purpose of this work was to conduct a high through put screening (HTPS) of over 2500 natural plants, OTC botanical supplements and phytochemicals to elucidate those with pro-inflammatory; toll like receptor 4 (TLR4) activating properties in macrophages. Study Design: The HTPS was conducted on RAW 264.7 cells vs. lipopolysaccharide (LPS) E. coli 0111:B4, testing iNOS / nitric oxide production (NO2–) as a perimeter endpoint. The data show not a single drug/chemical/ phytochemical and approximately 98 % of botanicals to be immune idle (not effective) with only 65 pro-inflammatory (hits) in a potency range of LPS. Method validation studies eliminated the possibility of false artifact or contamination, and results were cross verified through multiple vendors/ manufacturers/lot numbers by botanical species. Lead botanicals were evaluated for plant concentration of LPS, 1,3:1,6-β-glucan, 1,3:1,4-β-D-glucan and α-glucans; where the former paralleled strength in vitro. LPS was then removed from plants using high-capacity endotoxin poly lysine columns, where bioactivity of LPS null “plant” extracts were lost. The stability of E.Coli 0111:B4 in an acid stomach mimetic model was confirmed. Last, we conducted a reverse culture on aerobic plate counts (APCs) from select hits, with subsequent isolation of gram-negative bacteria (MacConkey agar). Cultures were 1) heat destroyed (retested/ confirming bioactivity) and 2) subject to taxonomical identification by genetic sequencing 18S, ITS1, 5.8 s, ITS2 28S, and 16S. Conclusion: The data show significant gram negative MAMP biomass dominance in A) roots (e.g. echinacea, yucca, burdock, stinging nettle, sarsaparilla, hydrangea, poke, madder, calamus, rhaponticum, pleurisy, aconite etc.) and B) oceanic plants / algae’s (e.g. bladderwrack, chlorella, spirulina, kelp, and “OTC Seamoss-blends“ (irish moss, bladderwrack, burdock root etc), as well as other random herbs (eg. corn silk, cleavers, watercress, cardamom seed, tribulus, duckweed, puffball, hordeum and pollen). The results show a dominance of gram negative microbes (e.g. Klebsilla aerogenes, Pantoae agglomerans, Cronobacter sakazakii), fungus (Glomeracaea, Ascomycota, Irpex lacteus, Aureobasidium pullulans, Fibroporia albicans, Chlorociboria clavula, Aspergillus_sp JUC-2), with black walnut hull, echinacea and burdock root also containing gram positive microbial strains (Fontibacillus, Paenibacillus, Enterococcus gallinarum, Bromate-reducing bacterium B6 and various strains of Clostridium). Conclusion: This work brings attention to the existence of a functional immune bioactive herbal microbiome, independent from the plant. There is need to further this avenue of research, which should be carried out with consideration as to both positive or negative consequences arising from daily consumption of botanicals highly laden with bioactive MAMPS.